Clinical characteristics, HIV status, and molecular biomarkers in squamous cell carcinoma of the conjunctiva in Ghana. Issue 2 (10th January 2019) - Merz, Lauren E.; Afriyie, Osei; Jiagge, Evelyn; Adjei, Ernest; Foltin, Susan K.; Ludwig, Megan L.; McHugh, Jonathan B.; Brenner, J. Chad; Merajver, Sofia D.
Abstract: Background and aims: Conjunctival squamous cell carcinoma (CSCC) varies in incidence geographically from 0 to 1 case per 100 000 per year globally. Additionally, the incidence of CSCC is known to increase 49% for every 10° decrease in latitude. Since the onset of the AIDS epidemic, there has been a trend of increasing incidence of CSCC in Africa, and despite relatively stable levels of ultraviolet (UV) exposure, there is an observed 12 times greater risk of developing CSCC when individuals are infected with HIV. In this study, we aim to analyze the clinical characteristics and biomarkers of CSCC in Ghana. Methods: In this study, a registry review of patients from January 2011 to May 2016 with CSCC at Komfo‐Anokye Teaching Hospital in Kumasi, Ghana, was performed (n = 64). Tumor blocks of the CSCC were analyzed for the expression of various biomarkers. Results: In this study, the median age of onset of CSCC is 46.5 years old (range of 20–90 y old). Fifty one and a half percent (n = 33) of the cohort is female. There is a low rate of smoking and alcohol use in our CSCC cohort. Thirty‐nine percent (n = 12) of Ghanaian men with CSCC are HIV−, while only 12% (n = 4) of women are HIV−. Fifteen patients had metastasis to lymph nodes or other tissues, and we observed a statistically significant relationship between HIV infection and metastasis ( P  = 0.027, chi‐squared test). We observed no statistically significant relationship between known prognostic CSCC biomarkers and HIV status, age, or tumor stage. Conclusion: Better characterization of CSCC could have a profound impact on the prevention, early identification, and treatment of CSCC in Africa. A retrospective chart analysis and collection of tumor samples can be challenging in this region due to methods of record keeping and stigma attached to clinical data such as HIV testing and smoking and alcohol use. As a result, in this study, data were often incomplete leading to inconclusive results and analysis that should be interpreted with caution. Future studies should consider a prospective study design that gathers clinical data in a standardized format and ensures fresh tissue from CSCC tumors.